Small Price Index of College Students Based on EEG - ShuLi Huang; ZhenDong Mu; HuaLiang Wu; HuaBo Xiao (Institute of Advanced Engineering and Science, 2013)
Study of consumer psychology and consumer price index usually used questionnaire method; this method is very good at solving the macro problem, however, to specific numerical value index, used questionnaire method is difficult to determine, and there is always a certain doubt about the correctness of the results what used questionnaire method. Because of EEG can be true reflection of the true psychological characteristics of the subjects, the paper selects EEG analysis tool as the consumer price index. Subjects tested with the different combination of the different quantity of money, processed and analysis this three sets of subjects EEG data, by analyzing the time and amplitude of the N170 and P300 to study college students in the daily life of the small consumer index. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3299